Firm characteristics and their impact on voluntary disclosure for Singapore and Hong Kong listed companies. - Ng, Sharon Woan Yng. (2008)
This project examines firm characteristics (firm size, leverage, auditor type, ownershp structure and percentage of independent directors) and their impact on voluntary disclosures for companies in Singapore and Hong Kong.